Amphiphilic Janus nanoparticles for imaging-guided synergistic chemo-photothermal hepatocellular carcinoma therapy in the second near-infrared window. Issue 7 (17th February 2021) - Chen, Xiangjun; Zhang, Xiuping; Zhang, Lingyu; Gao, Yuzhou; Wang, Changrong; Hong, Wei; Zhao, Guodong; Li, Lu; Liu, Rong; Wang, Chungang
Abstract : The unique amphiphilic oleic acid-NaYF4 :Yb, Er/polydopamine Au nanoflower Janus NPs with the discrete multi compartment nanostructures as dual-drug delivery systems are fabricated, which exhibit a novel strategy for efficiently combating HCC. Abstract : Hepatocellular carcinoma (HCC) is one of the most common and deadly malignant tumors worldwide. With unsatisfactory effects of traditional systematic chemotherapy for HCC owing to its drug resistance, novel therapeutic strategies based on nanomaterials for HCC treatments are promising solutions. To solve the challenges of nanoparticles (NPs)-based drug delivery systems for potential clinical applications, we designed water soluble amphiphilic oleic acid-NaYF4 :Yb, Er/polydopamine Au nanoflower Janus NPs (OA-UCNPs/PDA-AuF JNPs) with discrete multi compartment nanostructures as dual-drug delivery systems (DDDSs). This unique nanostructure meets the requirements for containing hydrophobic hydroxycamptothecin/hydrophilic doxorubicin in divided spaces and releasing each drug from non-interfering channels under pH/near-infrared (NIR) dual-stimuli. The amphiphilic DDDSs were utilized to eradicate the tumor burden on a high-fidelity HCC model of a patient-derived xenograft (PDX), and represented an efficient strategy for defeating HCC using multi-modal imaging-guided dual-drug chemo-photothermal therapy in the second NIR window. In addition, the potential mechanisms of action for the DDDSs were evaluated.